Transformation of Phomopsis asparagi with green fluorescent protein using protoplasts. Issue 2 (3rd April 2018) - Zhang, Yueping; Qu, Huaxiang; Zhao, Ping; Wu, Luofa; Zhou, Jingsong; Tang, Yongping; Luo, Shaochun; Chen, Guangyu
Abstract: Phomopsis asparagi is a fungal pathogen that causes destructive stem blight disease in garden asparagus worldwide. The host-pathogen interactions and molecular mechanisms of its pathogenicity are poorly understood. In this study, a protoplast transformation approach mediated by polyethylene glycol (PEG) was established for P. asparagi, and green fluorescent protein (GFP) expression transformants were successfully obtained. The transformants were mitotically stable when grown on potato dextrose agar (PDA) plates amended with 100 μg mL −1 of hygromycin B after five successive subcultures without selective pressure. All of the analysed transformants were further confirmed by polymerase chain reaction (PCR) amplification with primers specific to the hygromycin B phosphotransferase ( hph ) gene and Southern blotting. Moreover, these transformants showed similar pathogenicity on garden asparagus spears compared with the wild type, although a difference in growth rate was observed in oatmeal agar (OA) plates. These GFP expression transformants will serve as useful tools for investigating host penetration and the invasive growth of this devastating fungal pathogen, as well as defining the nature of the host-pathogen interaction.